Ecological impacts of single-axis photovoltaic solar energy with periodic mowing on microclimate and vegetation - Li, Yudi; Armstrong, Alona; Simmons, Christopher; Krasner, Noah Z.; Hernandez, Rebecca R. (Frontiers in Sustainability, 2025)
Large, ground-mounted photovoltaic solar projects (GPVs) are expanding rapidly worldwide, driven by their essential role in climate change mitigation and the transition to a low-carbon economy. With the global market for tracking systems projected to increase annually by 32% in capacity by 2050, understanding their ecological impacts, including those from their operation and management (O&M), is critical but understudied. This study presents the first comprehensive evaluation of microclimate and vegetation mosaics within a conventional, single-axis GPV managed through regular mowing. In the state of California’s Great Central Valley (United States), we developed a novel experimental framework to characterize five distinct “micro-patches” that capture the full spectrum of microclimate and vegetation zones modulated by the tracking PV system and O&M. Over a 12-month period, we monitored nine above- and belowground microclimate variables and 16 plant ecology metrics across these micro-patches. Beneath PV panels, photosynthetically active radiation decreased by 89%, and wind speed slowed by 46%, while open spaces within the GPV footprint exhibited greater soil surface temperatures (+2.4°C) and accelerated moisture loss (+8.5%) during drought periods. Furthermore, PV panel rotation influenced shading patterns throughout the day, creating temporal variability in air temperature and vapor pressure deficit. Plant surveys identified 37 species, 86% of which were non-native. Marked differences in vegetation across micro-patches indicated that GPVs drive changes in plant community composition, structure, and productivity. Compared to open spaces, vegetation near and within the PV array footprint displayed greater species richness (+8.4%), taller maximum height (+21%), reduced coverage of sun-loving plants (−71%), and less dead biomass accumulation (−26%), from shade-driven effects. These findings suggest the consideration of micro-patch-specific maintenance strategies and nature-based solutions to control invasive, exotic plant species, conferring opportunities to enhance operational, ecological, and socioeconomic sustainability while redressing the twin crises of climate change and biodiversity loss simultaneously.